Association Between Nutrition Literacy and Overweight/Obesity of Adolescents: A Cross–Sectional Study in Chongqing, China - Li, Shengping; Zhu, Yuzhao; Zeng, Mao; Li, Zhourong; Zeng, Huan; Shi, Zumin; Zhao, Yong (Frontiers in Nutrition, 2022)
Objective: The burden of overweight and obesity in adolescents is increasing rapidly. This study aimed to assess the association between nutrition literacy and overweight/obesity among adolescents in China. Methods: This cross-sectional online study involving adolescents aged 10-18 years was conducted in September 2020 in 239 schools in Chongqing China. Overweight and obese adolescents were determined based on the International Obesity Task Force’s recommended age-sex-specific body mass index cutoff points. Nutrition literacy was measured using the “Nutrition literacy scale for middle school students in Chongqing (CM-NLS).” The CM-NLS included three subdomains (functional nutritional literacy, interactive nutrition literacy, and critical nutrition literacy). Multinomial logistic regression model was used to examine the association. Results: A total of 18 176 adolescents (49.8% girls) were included. The prevalence of overweight and obesity were 9.6% and 17.0%, respectively. Compared with those having a low nutrition literacy score (below median), those with a high score were less likely to be overweight and obese. The odds ratio (95% CI) for overweight was 0.87 (0.79-0.97) (nutrition literacy) and 0.81 (0.73-0.90) (functional nutritional literacy). The corresponding figures for obesity were 0.84 (0.77-0.91) and 0.73 (0.67-0.80), respectively. Significant interaction existed between age and nutrition literacy. The inverse association between nutrition literacy and overweight/obesity was significant among those in senior school but not among those in junior high school. Conclusion: Nutrition literacy was inversely associated with overweight/obesity among adolescents, especially those attending senior high schools.